STRATEGI PENGEMBANGAN ORGANISASI (ORGANIZATIONAL DEVELOPMENT) MTsN 2 KOTA LHOKSEUMAWE - Nurasiah Nurasiah; Zulkhairi Zulkhairi (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
Organizational development (organizational development) in schools is strongly influenced by school support, therefore school business for organizational development can be carried out through school communities, such as school principals, teachers, staff, and community environment, by implementing organizational development strategies. The purpose of this study is to describe the strategy and inhibiting factors for organizational development (organizational development) MTsN 2 Lhokseumawe City. The method used in this study is a qualitative method with a descriptive approach. Data collection using observation techniques, interviews (interviews) and documentation. Data analysis is descriptive qualitative through data reduction, data presentation and drawing conclusions. The results of the study were found that schools played an important role in the development of organizations, especially school principals, teachers and school communities in supporting every organization's activities and cooperating with outside parties in developing and implementing organizational development strategies through efforts to plan organizational development strategies, formulation of organizational development strategies, organizing organizational development strategy, decision making and evaluation for the development of school organizations. The inhibiting factor in the development of school organizations is that there are some aspects that have not been fully proven by the objectives, Among other things, there is still a lack of discipline in working and related to the process of planning a school work program strategy, there are still obstacles faced, namely the lack of coordination and not yet optimal in the community environment and the lack of students' understanding of the importance of the organization and the time to participate in organizational activities.